Mucosal melanoma: report of case involving the oral cavity - Rodrigues-Fernandes, Carla Isabelly; Leite, Amanda Almeida; Souza, Ricardo Salgado de; Vargas, Pablo Agustin; Villalba, Halbert (Journal of Oral Diagnosis, 2020)
Primary oral mucosal melanoma (POMM) is a rare neoplasm derived from melanocytes, with unknown aetiology, and different presentation than cutaneous melanoma. It mostly affects the palate and maxillary alveolar ridge, with aspects that may mimic different lesions. Microscopically, POMM is characterized by the presence of medium to large atypical melanocytes with diverse morphologies. This neoplasm still presents challenges with regards to an appropriate treatment, and the overall prognosis is dismal. The aim of this report is to show a case of POMM in a 68-year-old female patient, who was diag- nosed due to an extensive and painful oral mass. Although the microscopic diagnosis can be straight-forward for some tumours, most data regarding the biological behaviour of POMM remains uncertain. Detailed microscopic immunohistochemical assessment are essential to elucidate the diagnosis of POMM.